Dosimetry and verification of (60)Co total body irradiation with human phantom and semiconductor diodes - Allahverdi, Mahmoud (Medknow Publications, 2007)
Total Body Irradiation (TBI) is a form of radiotherapy used for patients prior to bone marrow or stem cell transplant to destroy any undetectable cancer cells. The dosimetry characteristics of a (60)Co unit for TBI were studied and a simple method for the calculation of the prescribed dose for TBI is presented. Dose homogeneity was verified in a human phantom. Dose measurements were made in water phantom (30 × 30 × 30 cm(3)), using farmer ionization chamber (0.6 cc, TM30010, PTW) and a parallel plate ionization chamber (TM23343, PTW). Point dose measurements for AP/PA irradiation were measured in a human phantom using silicon diodes (T60010L, PTW). The lung dose was measured with an ionization chamber (0.3 cc, TM31013). The validity of the proposed algorithm was checked at TBI distance using the human phantom. The accuracy of the proposed algorithm was within 3.5%. The dose delivered to the mid-lobe of the lung was 14.14 Gy and it has been reduced to 8.16 Gy by applying the proper shield. Dose homogeneity was within ±7% for all measured points. The results indicate that a good agreement between the total prescribed and calculated midplane doses can be achieved using this method. Therefore, it could be possible to use calculated data for TBI treatments.